2003
DOI: 10.1557/jmr.2003.0064
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface cracking during indentation on hybrid coatings on polycarbonate

Abstract: Subsurface cracking after nano-and Vickers indentation on transparent silica-(meth)acrylate hybrid coatings deposited on a polycarbonate substrate was observed for the first time. It appeared that after initiation at the interface, these cracks propagated toward the surface and in radial directions as the indentation load increased. It was found that, for chemically identical coatings, the thicker the coating, the higher load necessary to initiate these cracks. Subsurface cracks formed during nanoindentation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The low φ c found for our cross-linked Phthalcon 11/epoxy composites can be explained by the fractal nature of our primary particle and secondary particle aggregates. It is well-known that both can lower considerably the φ c of conductive nanofiller polymer matrix composites. ,,,, This can be understood as follows. The percolating network can be considered as a network build of N spherical building blocks or blobs with radii R inside a composite volume V .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The low φ c found for our cross-linked Phthalcon 11/epoxy composites can be explained by the fractal nature of our primary particle and secondary particle aggregates. It is well-known that both can lower considerably the φ c of conductive nanofiller polymer matrix composites. ,,,, This can be understood as follows. The percolating network can be considered as a network build of N spherical building blocks or blobs with radii R inside a composite volume V .…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the factors which account for such a low φ c are complicated and partly unknown. It has been reported that the properties of the fillers, such as size, aspect ratio, and surface properties, the properties 1,2 of the matrix including viscosity and crystallinity, , the interfacial energy between the particles and the matrix, ,, and the quality of the nanoparticle dispersion may influence the percolation threshold. ,, However, currently only a few models exist which take into account some of these factors and by which some of the experimental results found could be explained. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation